2018
DOI: 10.1177/2397847318794859
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to ambient particulate matter induces oxidative stress in lung and aorta in a size- and time-dependent manner in rats

Abstract: Exposure to particulate matter (PM) has been implicated in oxidative stress (OxS) and inflammation as underlying mechanisms of lung damage and cardiovascular alterations. PM is a chemical mixture that can be subdivided according to their aerodynamic size into coarse (CP), fine (FP), and ultrafine (UFP) particulates. We investigated, in a rat model, the induction of OxS (protein oxidation and antioxidant response), carcinogen-DNA adduct formation, and inflammatory mediators in lung in response to different airb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 81 publications
(125 reference statements)
0
25
1
Order By: Relevance
“…Similar increases in the levels of HO-1 and NOX in the lung and heart have been reported after particle exposure in rats; the differences were dependent on particulate size ( Aztatzi-Aguilar et al, 2015 ). However, contrary to our findings, a recent study by OG Aztatzi-Aguilar reported a significant increase in SOD2 mRNA expression in the aorta of rats exposed to PM when compared to those in the filtered air group ( Aztatzi-Aguilar et al, 2018 ). One explanation for this discrepancy is that the mRNA expression of SOD2 might have been elevated at the beginning of PM exposure in the previous study to increase the anti-oxidation ability of the myocardial cells and resist free radical damage.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar increases in the levels of HO-1 and NOX in the lung and heart have been reported after particle exposure in rats; the differences were dependent on particulate size ( Aztatzi-Aguilar et al, 2015 ). However, contrary to our findings, a recent study by OG Aztatzi-Aguilar reported a significant increase in SOD2 mRNA expression in the aorta of rats exposed to PM when compared to those in the filtered air group ( Aztatzi-Aguilar et al, 2018 ). One explanation for this discrepancy is that the mRNA expression of SOD2 might have been elevated at the beginning of PM exposure in the previous study to increase the anti-oxidation ability of the myocardial cells and resist free radical damage.…”
Section: Discussioncontrasting
confidence: 99%
“…Catalase (CAT) serves as a protective enzyme that breaks down H 2 O 2 and eliminates ROS formation. Some studies have shown that exposure to PM 2.5 induces a loss of SOD2 and CAT activity, leading to an accumulation of ROS [24]. PM 2.5 has also been observed to downregulate protein kinase B (Akt) signaling, which is a known modulator of SOD2 and NFE2L2, decreasing the expression of SOD2 and NFE2L2 [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Many of the adverse health effects of PM 2.5 exposure are hypothesized to be derived from oxidative stress, which is initiated by the formation of reactive oxygen species (ROS) within cells [24]. Although several studies have demonstrated the ROS potential and inflammatory action of diesel particulates from diesel engine combustion, the causative factors are less clear.…”
Section: Introductionmentioning
confidence: 99%
“…Protein carbonylation has also been reported as a biomarker of oxidative stress-induced protein damage and has been associated with the development of cardiovascular and respiratory diseases [22,23]. A few studies have shown that protein carbonylation is increased in PM2.5-treated human keratinocytes and rat epithelial lung cells [24,25]. Thus, while cytokine expression and protein carbonylation may serve as important biomarkers for numerous lung diseases, their role in PM2.5-induced lung inflammation has not been extensively investigated in human cells.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the adverse health effects of PM2.5 exposure are hypothesized to be derived from oxidative stress, initiated by the formation of reactive oxygen species (ROS) within cells [25]. Though several studies have demonstrated the ROS potential and inflammatory action of diesel particulates from diesel engine combustion, the causative factors are less clear.…”
Section: Introductionmentioning
confidence: 99%